PRODUK BINAAN PANTI SOSIAL BINA REMAJA MARSUDI PUTRA TENGKU YUK PEKANBARU (STUDI KASUS ALUMNI PANTI BERDOMISILI DI KOTA PEKANBARU) - Annisa Nadhilah; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was implemented in Pekanbaru by taking alumni’s data that already graduated from UPT Social Institution of Adolescent Development “Marsudi Putra Tengku Yuk Pekanbaru” 4 years ago. The purpose of this research is to analyze the behavior of the alumni and the results of training skills after graduated from UPT Social Institution of Adolescent Development “Marsudi Putra Tengku Yuk Pekanbaru”. The focus of this research is the educational skill of alumni after graduating from institution. The sample of this research were 6 (six) people. The writer used qualitative descriptive methods and the data were analyzed in qualitative way and used purposive sampling technique. The instrument of this data is observation, deep interview and documentation. From this research, the writer found out that in looking at the results of education skills of alumni are with the following : there are two results of training skills that given while the alumni were still in institution. They are Motorcycle Automotive Skills and Welding Skills. Inside of those two training skills, there are curriculum and results of training, Study Practice Work, The Use of Instruments, and The Work of Respondents. Next are about The Change of Bad Behavior, The Worship Behavior, and The Behavior towards their Parents. The Change of Bad Behavior is about the changing of respondents bad behaviour before and after following social training in institution. The Worship Behavior, that there are some respondents who had increased their Worship Behavior and some others are stay still. The Behavior towards their Parents is the changing of the respondents’ behaviour towards their parents before and after following social training in institution.Keyword : Behavior, Results of Training Skills, Alumni of Institution